2018
DOI: 10.3892/or.2018.6202
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 expression in activated pancreatic satellite cells promotes fibrosis in chronic pancreatitis/pancreatic cancer via the TGF-β1/Smad pathway

Abstract: Chronic pancreatitis/pancreatic cancer (CP/PC) is characterized by fibrous connective tissue proliferation induced by activated pancreatic stellate cells (PSCs). Galectin-1 is upregulated in activated PSCs and is important for the continuing activation of PSCs. The aim of this study was to evaluate the effect of galectin-1 derived from activated PSCs on the progression of fibrosis in CP/PC. To this end, the expression of desmin, α-SMA, galectin-1, fibronectin and collagen type I in normal pancreatic, CP and PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…Subretinal fibrosis is a serious complication associated with CNV, leading to permanent vision loss in neovascular AMD (4, 6, 7, 13). Galectin-1 was shown to enhance the TGF-b-SMAD pathway, thus leading to the development of pulmonary and pancreatic fibrosis (19,20). To evaluate the lesion area of CNV-associated fibrotic tissues, composed mainly of type I collagen, we labeled flat mounts of the RPE-choroid complex with anti-type I collagen antibody at postlaser d 7 (Fig.…”
Section: Lgals1 Deficiency Suppresses Cnv-associated Subretinal Fibromentioning
confidence: 99%
See 1 more Smart Citation
“…Subretinal fibrosis is a serious complication associated with CNV, leading to permanent vision loss in neovascular AMD (4, 6, 7, 13). Galectin-1 was shown to enhance the TGF-b-SMAD pathway, thus leading to the development of pulmonary and pancreatic fibrosis (19,20). To evaluate the lesion area of CNV-associated fibrotic tissues, composed mainly of type I collagen, we labeled flat mounts of the RPE-choroid complex with anti-type I collagen antibody at postlaser d 7 (Fig.…”
Section: Lgals1 Deficiency Suppresses Cnv-associated Subretinal Fibromentioning
confidence: 99%
“…In addition to angiogenesis, galectin-1 has also been reported to be involved in mesenchymal activity via SMAD2 signaling in various cells, including gastric cancer cells, pancreatic stellate cells, and fibroblasts (19)(20)(21). Galectin-1 induced the phosphorylation of SMAD2 through its molecular interaction with SMAD2 in lung fibroblasts (19), thus promoting pulmonary fibrosis (19,22).…”
mentioning
confidence: 99%
“…MMPs and TIMPs are produced by hepatocytes in early stage of liver injury . TGF‐β1 mediates the balance of MMPs/TIMPs through Smad‐dependent pathway . Moreover, retinoic acid destructs MMP9/TIMP1 balance via the activated TGF‐β/Smad pathway, which disturbs ECM formation …”
Section: Introductionmentioning
confidence: 99%
“…37 TGF-β1 mediates the balance of MMPs/TIMPs through Smaddependent pathway. 38 Moreover, retinoic acid destructs MMP9/TIMP1 balance via the activated TGF-β/Smad pathway, which disturbs ECM formation. 39 According to the researches above, we hypothesized that Nano NiO could induce hepatic fibrosis, which might be related to TGF-β1-mediated Smad and MAPK pathways and EMT occurrence in vivo and in vitro.…”
mentioning
confidence: 99%
“…9,10 Therefore, activation of PSCs is considered a core event in pancreatic fibrosis. 11,12 Epithelial mesenchymal transition (EMT) is a biological phenomenon in which epithelial cells lose epithelial properties to obtain stromal cell phenotypes. Recent studies confirmed the role of EMT in fibrosis of organs such as the lungs and the liver.…”
Section: Introductionmentioning
confidence: 99%